2021
DOI: 10.3846/tede.2021.15374
|View full text |Cite
|
Sign up to set email alerts
|

Expenditure Fluctuation and Consumption Loss: Rural Spatial Poverty in China

Abstract: Poverty is a challenge faced by all countries worldwide. This paper focuses on a factor that has been less well documented: the consumption loss of farmer households caused by the fluctuation of rural public expenditure. Based on large-scale micro household data and climate data, the instrumental variable estimation results show that every 1% fluctuation of rural public expenditure will lead to a 0.113% decrease in farm household consumption. In addition, the fluctuation of rural public expenditure is also a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…From the dimension of financial resources, the implementation of environmental policy in different places usually depends on central financial incentives and local financial capacity (Dunlop and Corbera, 2016;Qi and Zhang, 2014), and sufficient financial resources are an important guarantee for local governments to implement environmental governance (He et al, 2012;Tacconi et al, 2008), while when there is a large financial pressure, it changes local government behavior, making local governments pay more attention to economic growth and neglect the environment, and this incentive effect formed by financial pressure is This incentive effect formed by fiscal pressure is an important reason for the growth of industrial pollution in China (Hui et al, 2022). In contrast, the implementation of the poverty alleviation policy has led the state to increase the intensity of investment in poverty alleviation funds in counties (Luo et al, 2021), and the financial transfer payments shared at the central, provincial, counties, and county levels have reconciled the contradictions between the central and local governments in terms of financial resources (financial power) and environmental governance matters (affairs) (Gong et al, 2020), bringing an increase in the level of financial security of local governments (Su et al, 2021;Wen and Lee, 2020), which has helped to alleviate the financial pressure on local contributes to the improvement of urban productivity and resource use efficiency (Hou et al, 2022;Hui et al, 2022), significantly increases the willingness and motivation of local governments to protect the environment (Zhang and Zhao, 2018), and therefore this will help localities to improve the environmental quality situation. Accordingly, this paper proposes hypotheses two and three:…”
Section: Theoretical Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the dimension of financial resources, the implementation of environmental policy in different places usually depends on central financial incentives and local financial capacity (Dunlop and Corbera, 2016;Qi and Zhang, 2014), and sufficient financial resources are an important guarantee for local governments to implement environmental governance (He et al, 2012;Tacconi et al, 2008), while when there is a large financial pressure, it changes local government behavior, making local governments pay more attention to economic growth and neglect the environment, and this incentive effect formed by financial pressure is This incentive effect formed by fiscal pressure is an important reason for the growth of industrial pollution in China (Hui et al, 2022). In contrast, the implementation of the poverty alleviation policy has led the state to increase the intensity of investment in poverty alleviation funds in counties (Luo et al, 2021), and the financial transfer payments shared at the central, provincial, counties, and county levels have reconciled the contradictions between the central and local governments in terms of financial resources (financial power) and environmental governance matters (affairs) (Gong et al, 2020), bringing an increase in the level of financial security of local governments (Su et al, 2021;Wen and Lee, 2020), which has helped to alleviate the financial pressure on local contributes to the improvement of urban productivity and resource use efficiency (Hou et al, 2022;Hui et al, 2022), significantly increases the willingness and motivation of local governments to protect the environment (Zhang and Zhao, 2018), and therefore this will help localities to improve the environmental quality situation. Accordingly, this paper proposes hypotheses two and three:…”
Section: Theoretical Mechanismsmentioning
confidence: 99%
“…Robustness test based on sample size. To ensure the robustness of the regression results and to exclude the possible influence of outliers of the variables on the estimation results, the control variables below the 5% and above the 95% quantile are replaced by the 5% and 95% quantile, respectively, and the corresponding results are shown in column (6) of Table 3. The policy of poverty alleviation can significantly improve the level of environmental quality in the county, which proves that the estimation results are robust.…”
Section: Truncation Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, some studies have begun to draw on the geographic school of thought to identify the spatial distribution of poverty, finding that there is a clear spatial poverty trap (SPT) in rural China [22,23]. One study revealed the impact of spatial externality on rural poverty from the perspective of public expenditure fluctuation [24], where a spatial scale effect was found to exist in regional poverty features and in the impact of geographical capital on regional poverty [25].…”
Section: Introductionmentioning
confidence: 99%
“…The construction land has low economic and social output and huge resource consumption, pollution and emissions, which is not conducive to the highquality development of cities. For a long time, Chinese government has paid great attention to the intensive use of land and has issued a series of related guidelines and regulation policies (Luo et al, 2021). The Suggestions on Construction Supervision and Implementation of a Land Spatial Planning System in 2019 clearly proposed to define the spatial boundaries such as ecological redline, permanent basic farmland and urban development boundary, to enhance the constraint of the bottom line and reserve space for sustainable development.…”
Section: Introductionmentioning
confidence: 99%